Fungal infection and neurodevelopmental outcomes at 18–30 months in preterm infants - Zhou, Qi; Kelly, Edmond; Luu, Thuy Mai; Ye, Xiang Y.; Ting, Joseph; Shah, Prakesh S.; Lee, Shoo K. (Frontiers in Pediatrics, 2023)
Background Invasive fungal infection (IFI) is associated with significant mortality and morbidity among preterm infants but there has been no population-based study of long-term neurodevelopmental outcomes. The objective of this study was to examine population-based incidence trends as well as mortality, short term in-hospital morbidity and long-term neurodevelopmental outcomes among preterm infants with IFI, non-fungal infections (NFI) and no infections in Canada. Methods We conducted a retrospective cohort study of 8,408 infants born at <29 weeks gestational age (GA), admitted to Canadian Neonatal Network neonatal intensive care units (NICU) from April 2009 to December 2017, and followed up at 18–30 months corrected age (CA) in Canadian Neonatal Follow-Up Network clinics. We compared mortality, long term neurodevelopmental outcomes and short term in-hospital morbidity among 3 groups of infants (IFI, NFI, and no infections). Results The incidence of IFI was 1.3%, non-IFI 26.9% and no infections 71.7%. IFI incidence varied between 0.93% and 1.94% across the study period with no significant trend over time. Infants of higher gestational age were significantly (p < 0.01) less likely to have IFI. Among infants with IFI, NFI and no infections, the incidence of the significant neurodevelopmental impairment (sNDI) was 44.26%, 21.63% and 14.84% respectively, while mortality was 50%, 25.35% and 22.25% respectively. Even after risk adjustment for confounders (GA, Score for Neonatal Acute Physiology Version II, ruptured membranes >24 h, maternal antibiotic treatment, antenatal steroid use, cesarean section), infants with IFI had significantly higher odds of sNDI than NFI (aOR: 2.19; 95% CI: 1.23, 3.91) or no infections (aOR: 2.97; 95% CI: 1.55, 5.71), and higher odds of mortality than NFI (aOR: 1.55; 95% CI: 1.07, 2.26) or no infections (aOR: 1.45; 95% CI: 0.97, 2.17). Conclusions Preterm infants with invasive fungal infections have significantly higher incidence of mortality and adverse neurodevelopmental outcomes than those with non-invasive fungal infections and no infections.